Rapid Diagnosis of Metabolic Disorders Based on Achiral Separation by Gas Chromatography with a Dual Column - Lee, Jaeick; Yoon, Hye-Ran (TAYLOR & FRANCIS INC, 2015)
In some metabolic diseases, a known specific chiral isomer is excreted to urine or blood and, thus, identification of its absolute configuration is critical to determining the course of diagnostic and therapeutic management (e.g., L-2-hydroxy glutaric aciduria). Chiral organic acids extracted from acidified urine with diethyl ether were subjected to (-)-menthylation or (S)-(+)-3-methyl-2-butylation with subsequent O-trifluoroacylation to form volatile diastereomeric esters. Each enantiomer was unequivocally discriminated with achiral dual columns (nonpolar and medium-polar columns) cooperating with retention index (I) library matching. D, L-lactic acid, D, L-2-hydroxybutyric acid, D, L-3-hydroxybutyric acid, and D, L-2-hydroxyglutaric acid were correctly identified by chiral separation from the urine samples of ten patients with various metabolic disorders. Achiral simple dual column gas chromatography provided adequate sensitivity for the separation of volatile diastereomeric derivatives. This approach may be a useful tool for differential diagnosis of inborn metabolic disease in which chiral acid is excreted.
Keywords: TANDEM MASS-SPECTROMETRY; SHORT-BOWEL SYNDROME; D-GLYCERIC ACIDURIA; L-2-HYDROXYGLUTARIC ACIDURIA; D-2-HYDROXYGLUTARIC ACIDURIA; 2-HYDROXYGLUTARIC ACID; CHIRAL COMPOUNDS; DEHYDROGENASE; DEFICIENCY; DISEASE